Dampak Kurikulum Merdeka Terhadap Karakteristik Peserta Didik Sekolah Dasar - Aulia, Serly; Sharyna; Mauli Daini, Ulfa; Virany, Tima; Luis Carlo Fatana, M. Aurel; Abdurrahmansyah (UNIB Press, 2025)
This study aims to provide a deep understanding of the impact of the Independent Curriculum on the characteristics of elementary school students using a qualitative approach. The background of the study began with concerns that the characteristics of elementary school children who still require intensive guidance do not fully align with the demands of the Independent Curriculum, which encourages independent learning and group discussions. The research method used a qualitative approach through observation and interviews with teachers and students in several elementary schools. The research stages included data collection, analysis of students' abilities in discussions, problem-solving, and presentations, and evaluation of the teacher's role in learning. The results showed that although the Independent Curriculum provides space for the development of independent skills, the characteristics of elementary school children who still require full guidance cause difficulties in its implementation, especially for passive or slow students. The discussion highlights the need to adjust learning methods and media that are more appropriate to the developmental stage of elementary school students so that the objectives of the Independent Curriculum can be optimally achieved.